Productive Zakat Management in Empowering Micro Business for Poverty Alleviation (Study at Baznas Mandailing Natal District - Fahrizal Harahap, Mufti; Jureid, Jureid; Hamdanil, Hamdanil (ILTIZAM Journal of Shariah Economics Research, 2025)
This study is to study productive zakat management implemented by BAZNAS Regency Mandailing Christmas in microbusiness empowerment. For alleviation of poverty. Productive zakat is used as an instrument of Islamic economics to increase the welfare of mustahik through business capital assistance , mentoring, and entrepreneurship training. Research This use method approach is qualitative in nature and descriptive with type studies and case studies, where data is obtained through in-depth interviews, direct observation, and document analysis. Research results show that the scheme distribution of productive zakat at BAZNAS Mandailing Natal includes working capital grants, qardhul hasan (virtuous loans without interest ), and partnerships based on results. This program gives a positive impact to improving the income of mustahik as well as pushing independent microbusinesses. However , the challenges in the implementation of productive zakat Still faced , such as limited funds, low literacy finance mustahik , as well as not yet optimal implementation of standard accounting (PSAK 109). Research conclusions This emphasize importance more productive zakat management​ transparent and professional , with support mentoring systematic effort . The recommendation study covers the improvement of BAZNAS HR capacity in management finance , optimization of synergy with government and institutions of sharia finance, and digitalization of system data collection and monitoring of mustahik. With good governance , productive zakat can become an effective instrument​ to eradicate poverty and increase welfare in a sustainable way.